Impact of single dose versus multidose prophylactic antibiotics in elective hernia repair: an institutional study - Durai, Ramula M.; Mohamed, Noorul (International Surgery Journal, 2021)
Background: Antibiotics used prophylactically in anticipation of surgery-related infection are not indicated for elective surgical procedures where the chance of infection is very low and the expected benefit of antimicrobial treatment is not well documented. Routine prophylactic use of antibiotics in clean cases and the difficulty in balancing the benefits of the intervention with the potential adverse drug reaction is debatable. There are not much randomized, controlled trials or patient-specific information to assess his balance precisely, but only general guidelines for the clinician to decide for his patients. This study was conducted in our Institute to inquire the basis that prevention of surgery related infection in elective groin hernia repairs equally effective when patients were given either preoperative single-dose or multi-dose antibiotics postoperatively. Methods: This prospective, longitudinal study, 100 eligible patients who were admitted for elective hernioplasty, were randomly assigned in two equal groups with 50 each. Single dose (SD) group was given a single antibiotic of 2 gm parental amoxycillin-clavulanic acid at the time of induction of anesthesia. The multidose group was given through intravenous route same antibiotic (2 gm) preoperatively followed by amoxycillin-clavulanic acid (1 gm) twice a day for two days in their post-operative period also and their effect compared. Results: In the single-dose prophylactic antibiotic group (group I) the surgery related infection rate was only 8%, compared to those who received postoperative multiple-dose groups (group II). Conclusions: The postoperative wound-related infection rate after a single dose antibiotic parenterally at the induction of anesthesia is favorably compared with that of multiple-dose antibiotics.